1991
DOI: 10.1007/bf01800008
|View full text |Cite
|
Sign up to set email alerts
|

An occipito‐temporal syndrome in adolescents with optimally controlled hyperphenylalaninaemia

Abstract: The study included 16 adolescents with optimally controlled hyperphenylalaninaemia (McKusick 26160), of whom six did not require treatment according to conventional criteria. All except the two patients with lowest median serum phenylalanine level throughout childhood (most values at 200-300 mumol/L) had white matter abnormalities detectable with magnetic resonance imaging. The lesions were particularly prominent in the watershed regions between the posterior and middle cerebral arteries. In most patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 12 publications
3
29
0
Order By: Relevance
“…In all patients, spectra were obtained at TE = 270 ms to optimize lactate detection [21], however in none a definite lactate peak was found. Our findings correspond well with results recently published by Lou et al [35], who also found normal proton spectra in two patients with HPA. Johannik et al [28] observed a reduction in relative inositol concentration in PKU patients using a shorter echo time (TE = 20 ms).…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…In all patients, spectra were obtained at TE = 270 ms to optimize lactate detection [21], however in none a definite lactate peak was found. Our findings correspond well with results recently published by Lou et al [35], who also found normal proton spectra in two patients with HPA. Johannik et al [28] observed a reduction in relative inositol concentration in PKU patients using a shorter echo time (TE = 20 ms).…”
Section: Discussionsupporting
confidence: 95%
“…Regression of MRI abnormalities after reinstitution of strict diet treatment has also been reported by two other groups [5,52]. Our data as well as the data from the literature indicate, that a significant regression of MRI white matter abnormalities under diet may only be expected with plasma Phe levels below 0.36 mmol/l [35]. This range of Phe values corresponds well to plasma Phe concentrations which are considered safe during early childhood [50].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Recent advances in brain imaging have also shown abnormalities in patients with PKU. Magnetic resonance imaging (MRI) has shown abnormalities in the white matter of the brain in asymptomatic, early-treated children and adults (6,7). These MRI abnormalities were related to recent levels of Phe and length of time since dietary treatment ceased, and were independent of Phe levels early in life (6).…”
mentioning
confidence: 99%